1997
DOI: 10.1152/jn.1997.77.6.3168
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Masticatory Force During Cortically Induced Rhythmic Jaw Movements in the Anesthetized Rabbit

Abstract: To examine the relationships between masticatory force, electromyogram (EMG) of masticatory muscles, and jaw movement pattern, we quantitatively evaluated the effects of changing hardness of a chewing substance on these three variables. Cortically induced rhythmic jaw movements of a crescent-shaped pattern were induced by electrical stimulation of the cerebral cortical masticatory area in the anesthetized rabbit. The axially directed masticatory force was recorded with a small force-displacement transducer mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 55 publications
3
67
0
Order By: Relevance
“…If so, periodontal afferents and -motoneurons must have evolved to serve other functions in mammals [e.g. feedforward control of mammalian chewing enabled by periodontal afferents and -motoneurons (Hidaka et al, 1997) likely reduces the degree of tooth wear and the probability of tooth fracture during mastication], leaving lepidosaurs unusual in their low degree of rhythmicity. In support of this hypothesis, chewing rhythmicity is seen in the basal osteichthyan lungfish Lepidosiren paradoxa (Bemis and Lauder, 1986).…”
Section: Rhythmicity Efficiency and Sensorimotor Evolution In Vertebmentioning
confidence: 99%
See 1 more Smart Citation
“…If so, periodontal afferents and -motoneurons must have evolved to serve other functions in mammals [e.g. feedforward control of mammalian chewing enabled by periodontal afferents and -motoneurons (Hidaka et al, 1997) likely reduces the degree of tooth wear and the probability of tooth fracture during mastication], leaving lepidosaurs unusual in their low degree of rhythmicity. In support of this hypothesis, chewing rhythmicity is seen in the basal osteichthyan lungfish Lepidosiren paradoxa (Bemis and Lauder, 1986).…”
Section: Rhythmicity Efficiency and Sensorimotor Evolution In Vertebmentioning
confidence: 99%
“…with low cycle duration variance) by enabling feedforward modulation of MAPs during the slow close phase of the gape cycle (SC) in response to variation in food material properties within and between chewing sequences (Hidaka et al, 1997). In support of this hypothesis, Ross and colleagues showed that mammalian chew cycle durations not only are less variable than those of lepidosaurs but also increase with mandible length, which does not occur among lepidosaurs.…”
Section: Introductionmentioning
confidence: 99%
“…There is only limited knowledge regarding activity pattern changes in the jaw closing and opening muscles, although qualitative changes have been described using visual observations [5,6] and not specific, appropriate parameters for assessing activity patterns. Consequently, it is challenging to compare our results to those of other investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons of either or both nucleus groups send action potentials, via the parvocellular reticular nucleus, to the jaw opening and closing motoneurons, innervating the muscles responsible for chewing movement [4]. Activity of the jaw opening muscles during fictive chewing affects the activity of the jaw closing muscles via action potentials from the sensory apparatus of the muscle spindles and periodontal pressoreceptors, which are located in the orofacial region of animals [5][6][7][8] including humans [9][10][11]. Opening of the jaw stretches the muscle spindles of the jaw closing muscles, and the stretch reflex then contracts the muscles; conversely, closing of the jaw muscles during chewing is unlikely to affect jaw opening muscle activity [12], partly due to the lack of muscle spindles in the jaw opening muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation